Analisis Perbandingan Akad Murabahah dan Akad Musyarakah Mutanaqisah (MMQ) Pada Pembiayaan KPR (Studi Kasus Pada Bank Syariah Indonesia Kantor Cabang Pembantu Bogor Ahmad Yani) - Fitriani, Ucu; Abdul Syukur, R. Dudung; Faizal, Harun (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Banks have various products that aim to support the needs of the community. One of these products is mortgage financing (KPR), according to the population and civil registration office, the population of Indonesia was 282,477,584 in the first semester of 2024 and will continue to grow. This indicates that housing is an important need for people to support their lives. The purpose of this study is to provide access to solutions for the community to own a house easily and to gain a deeper understanding of financing based on sharia principles. The methodology used in this study is a qualitative method with field research . Data collection was conducted through observation, interviews, and documentation, and the data was then analyzed using descriptive analysis methods. The results of this study show that the Musyarakah Mutanaqisah contract is considered more suitable for use at BSI KCP Bogor Ahmad Yani compared to the Murabahah contract. This is supported by data on the number of financing customers in 2024, with 1,300 customers using the Musyarakah Mutanaqisah contract compared to 900 customers using the Murabahah contract.